Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/1758-5090/ab4647
|View full text |Cite
|
Sign up to set email alerts
|

Biomanufacturing of a novel in vitro biomimetic blood-brain barrier model

Abstract: A glioma is a malignant tumor that severely threatens human health. However, it is difficult for most therapeutic agents to penetrate through the blood-brain barrier (BBB) and exhibit their antineoplastic activity in the brain. In this article, a biomimetic in vitro BBB model was created by a composite process, this model can provide a significant foundation for the research of drug transport, tumor treatment, tumor microenvironment and other fields. A series of tests and comparative experiments were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Coaxial nozzles have an outer layer, which produces the sheath, and an inner layer, which produces the core. Nozzle sizes vary greatly depending on the application, and sheath nozzles with inner diameter up to 7 mm have been shown successful if proper curing and crosslinking procedures are implemented [ 21 ]. Core nozzle inner diameter can be as small as 210 μm [ 22 ].…”
Section: Bioprinter Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Coaxial nozzles have an outer layer, which produces the sheath, and an inner layer, which produces the core. Nozzle sizes vary greatly depending on the application, and sheath nozzles with inner diameter up to 7 mm have been shown successful if proper curing and crosslinking procedures are implemented [ 21 ]. Core nozzle inner diameter can be as small as 210 μm [ 22 ].…”
Section: Bioprinter Designmentioning
confidence: 99%
“…A notable and widely used physical crosslinking method is the reaction of alginate with divalent anions such as Ca 2+ . This reaction is quicker than most physical methods and requires a bath [ 21 ], aerosol spray [ 29 ], or inline flow of calcium ions [ 30 ]. A vacuum under the stage may be used to remove the excess ion solution as deposition occurs [ 30 ].…”
Section: Bioprinter Designmentioning
confidence: 99%
See 2 more Smart Citations
“…These models, however, typically result in unreliable results due to the lack of a similar microenvironment in vitro . Several studies have revealed that differences exist between the 2D and 3D cultures and across species [47]. This is why many “efficient” drugs that perform well lose their effects in clinical trials.…”
Section: Biomaterials and Biofabrication For Primary Neural Cell And ...mentioning
confidence: 99%